Early recovery after surgery in elective obstetrics-gynaecology surgeries: prospective single-center pilot study - Jain, Ritu V.; Jain, Vaibhav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Enhanced recovery after surgery (ERAS) programmes employed in elective colorectal, vascular, urologic and orthopaedic surgery has provided strong evidence for decreased hospital stay without increase in postoperative complications. The aim of the study was to explore role and benefits, if any, of ERAS/ERP (early recovery protocols) implemented in patients undergoing elective obstetrics-gynaecological surgeries. Methods: Prospective cohort of 48 consecutive patients undergoing elective obstetrics-gynaecological surgeries were included. ERP included early feeding, urinary catheter removal, mobilisation/physiotherapy, intravenous line removal and optimal oral analgesia. This was compared to control group of 50 patients undergoing similar operations prior to introduction of ERP, SPC group-standard perioperative care. Demographics and indications of surgeries were similar for both groups. The primary end-points were length of stay (LOS) and incidence of complications (Clavien-Dindo classification). Difference in means was tested using the t test assuming unequal variances. Statistical significance was defined as p<0.05. Results: Two groups, A (non-ERAS/SPC) and B (ERAS) were comparable with regards to demographics and indication of surgery. The mean time to solid diet, urinary catheter removal, mobilization, iv fluid removal and shift to oral analgesia was 2.57, 1.13 (p<0.00001), 1.99 ,1.03 (p<0.00268), 1.63, 1.2 (p<0.00001), 1.72, 1.14 (p<0.00001), 1.8, 1.37 (p<0.00001) days respectively. There were 31 and 21 complications in both groups, respectively (p<0.0097). Hospital stay was significantly shorter in the ERAS group, 2.87, 2.61 (p<0.0378). Conclusions: This pilot study shows that ERPs can be successfully implemented with significant shorter hospital stays without increase in postoperative complications in elective obstetrics-gynecology patients.